Gender Equality in Islamic Organizations: A Study on Nahdlatul Ulama - Reka Gunawan; Nurul Hariani; Alfan Taufiqi; Ali Aziz; Sokhi Huda (MUHARRIK: Jurnal Dakwah dan Sosial, 2022)
The existence of female leaders in an organization has an impact on gender equality in society. This impact happened to the Nahdlatul Ulama organization, the largest national Islamic institution with social and political influence. This study aims to describe the dynamics process and the existence of gender equality in the Islamic organization Nahdlatul Ulama. This study uses a qualitative field approach with a feminist perspective in organizational communication. The data were obtained through observations and interviews with the General Chairperson of Nahdlatul Ulama and the Chairperson of Tanzfidiyah. This research shows that Gender Equality in the dynamics of the Nahdlatul Ulama organization can be identified through the various roles performed by one of the female leaders, namely Khofifah Indar Parawansa, the Chair of Tanfidziyah in the 2022-2027 era. Shows that the role of women leaders in Nahdlatul Ulamais currently in a phase or period of free competition. Meanwhile, regarding the existence of Gender Equality in the Nahdlatul Ulama organization, it shows assumptions about the prediction that if the role of women leaders such as Mrs. Khofifah in the political and social fields is getting stronger, it will also have a strong influence on the existence of female cadres in Nahdlatul Ulama in the next period. This study argues that gender equality in Islamic organizations at Nahdlatul Ulama is a role model for other organizations.